Noblemen, Knights and Dukes: representation of the noble estate in Don Quixote - Maria de los Angeles Calvo (Estudios de Teoría Literaria, 2019)
To analyze the representation of the noble class in the first and the second part of Don Quixote, written ten years apart (1605 and 1615 respectively) we notice certain similarities, mainly that, in both cases, the characters of the nobility are quantitatively very lower level State-owned characters, and appearing in two parts by members of the high nobility and the lower nobility. However, the differences are much more significant because they realize a look different epochal in which the economic and social crisis has worsened, the imperial dream is slowly crumbling and new actors break into the social scene cracking the foundations of the Old Regime.